Usulan Strategi Bersaing Jasa Pengiriman Paket PT. POS Indonesia (Studi Kasus di UPT PT. POS Indonesia II BANDUNG) - Febriansyah, Ferry; Yuniarto, Paulus; Mutaqien, Zaenal (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2012)
As a BUMN in postal industry, PT. Pos Indonesia claimed to be survived in nowadays competition and also be able to give contribution to the government. To make it happen, it needs competitive strategy that match to the existing business, so that business can achieve the corporate goals. Strategies that will be conducted are correlated to the company's internal and external environment, including customer satisfaction. So with the analysis of environment and customer satisfaction, later on the company will be able to adapt for the change that happen in its business environment to its internal condition. Those things that make the writer recommend an appropriate formula of company's strategy that suitable with the internal and external condition of the company.To gather information about internal and external condition of the company, the writer uses a previous guestioner. With this guestioner, the writer knows the internal factors that strengths and weaknesses for the company and the external factors that could be either opportunities or threats to company. To know how big that environment influenced, we conducted a rating for those factors so we can know the company business position. This position can be known from GE (General Electric) Matrix which combined the industry attractiveness with business power. To know the customer satisfaction we use CSI (Customer Satisfaction Index), CSGI (Customer Satisfaction Gap Index), CSI Boxes, and Importance-Performance Matrix. With those things, we can formulate a competitive strategy that match to the company business environment.The result of this research, we know that business position of the company is on the selective growth level. About the customer satisfaction, the customer felt guit satisfy for the service that PT. Pos Indonesia gave with 63,38%of CSI. But if it's compared with Tiki, the guality service of PT. Pos Indonesia still loose.Aspect Industry Attractiveness, Score 3.82. Aspect Business Power, Score 3.61.The conclusion of this whole research is the formulating of business and functional level strategy. The formulated business strategies are growth strategy consist of market penetration, innovations, concentrations and alliance strategy. The functional strategies are the reduction of business strategies. The functional strategy conducted in marketing and distribution, operation, human resource, and financial section.